Menilik Peran Organisasi Kepemudaan TIDAR dalam Upaya Pengembangan Generasi Muda di Kota Bandar Lampung - Lanang Maulana; Nourel Islamay Diandra; Komang Windasari; Ana Mentari; Teki Prasetyo Sulaksono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Tunas Indonesia Raya (TIDAR) is a youth organization under the auspices of the Gerindra Party and focuses on increasing political awareness among the younger generation. This study aims to examine the role and challenges faced by TIDAR in carrying out its youth activities in Bandar Lampung City. Based on interviews with the local TIDAR Chairperson and observations of organizational activities, it is known that TIDAR routinely holds leadership training, political discussions, and social actions involving various youth groups. These initiatives contribute to forming a younger generation that is more aware of the role of politics and social concerns. However, the dynamics of membership and the limited time of members are obstacles in implementing the program. To maintain the sustainability of the organization, TIDAR Bandar Lampung continues to develop adaptive approach strategies such as open recruitment and strengthening internal communication. The presence of TIDAR in this area shows the important role of youth political organizations in facilitating the active participation of the younger generation in national and state life.